Outsourcing of employees – term review - Antczak, Barbara (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The concept of employee outsourcing has raised numerous doubts for years, mainly due to its identification with the notorious practices of employers aimed at evading the fulfillment of public law obligations related to the employment of employees. In this article, doctrinal and juridical definitions of this term will be confronted with the characteristics of the concept of outsourcing developed on the basis of management sciences. The remarks made in this way will serve to create an author’s definition of the concept of “employee outsourcing”.